THE POSSIBILITY OF CREATING MULTIFUNCTIONAL SILVER-CONTAINING DRUGS WITH DETOXIFYING EFFECT - T. V. Popova; N. O. Karabinceva; L. N. Rachkovskaya; T. G. Tolstikova; A. A. Kotlyarova; A. Yu. Letyagin (Фармация и фармакология (Пятигорск), 2017)
Modern technology and the level of fundamental studies allow us to create the medical sorbents with the predetermined structural, mechanical and adsorptional properties. Sorption materials are interesting not only as detoxicants that are used to remove toxic agents from the liquid media, but also as carriers for a delivery in zones a therapeutic effect of biologically active substances. The aim of this work is the substantiation of structure of the multifunctional drug with anti-bacterial and detoxifying effects due to the complex of silver and the sorption component – alumina-silica-containing sorbent. Materials and methods. We used physico-chemical (sorption activity of methylene blue dye, specific surface, pH in contact with water, atomic emission spectrometry with inductively coupled plasma) and pharmaceutical methods (bulk density, dissolution test for solid dosage forms). Results and discussion. The two-stage method of immobilization of a complex of silver and water repellent on the surface sorptionmatrix was justified. The sample of the optimum composition of silver-containing drugs was selected: aluminium oxide-hydroxide – 99.2%, clustered silver (Argovit – C – 2%) – 0.3 %, based on silver and subsidiary substance (repellents – brand PMS P – 841) – 0.5 %. The output of silver into the solution from the specified sample composition for 8 hours did not exceed 1,6 ± 0,3%, the value of specific surface area of 90 m2/ g, the value of pH to 8.1 ± 0.02, bulk density 1.12 ± 0.11 g/cm3. Conclusion. An experimentally substantiated composition of silver-containing drug AlSi/Ag was received, a comprehensive scientific data of its physico-chemical and technological properties were obtained.